An evaluation of small scale open cast mining of UG2 in the Bushveld complex - Mooney, David G (Rhodes University, Faculty of Science, Department of Geology, 1997)
The current weak state of the platinum market, as well as the large inventory of platinum group metals held by Russia, necessitates that the South African platinum mining industry must carefully evaluate the benefits and disadvantage of small-scale mining of shallow, open castable ore resources. Until the late 1980's, these resources were ignored due to the metallurgical complexities of treating oxidized ore, as well as the mind set that existed within the South African mining industry which militated against open cast mining in the Bushveld. During the latter part of the 1980's and early 1990's, advances in the metallurgical treatment of oxidized ore, specifically the UG2, as well as operational problems, created the impetus to begin the exploitation of these resources. Small-scale open cast mining has become viable due to the development of suitable mining methods that facilitate mining practices acceptable to the Department of Mineral and Energy Affairs, in terms of environmental legislation. Metallurgical advances and growing experience, especially with respect to the UG2, enables reasonable platinum group metals recovery from oxidized ore. The problems experienced in doing this can, and are being overcome. With growing public awareness of environmental issues, particularly related to the mining industry, the requirement to ensure that the small-scale open cast mine site is well managed is paramount. A methodology for the evaluation is presented along with a case study of a small-scale UG2 open cast pit. Evidence is presented that shows that these small-scale open cast mining operations are extremely profitable and require minimal capital expenditure. However, caution is advised when evaluating Merensky Reef open cast operations because of the problems that they present.
Keywords: Platinum mines and mining -- South Africa; Strip mining -- South Africa